2006
DOI: 10.1111/j.1440-1843.2006.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis drugs and hepatotoxicity

Abstract: Antituberculosis drugs and hepatotoxicity YEW WW, LEUNG CC. Respirology 2006; 11: 699-707 Abstract: Isoniazid, pyrazinamide and rifampicin have hepatotoxic potential, and can lead to such reactions during antituberculosis chemotherapy. Most of the hepatotoxic reactions are dose-related; some are, however, caused by drug hypersensitivity. The immunogenetics of antituberculosis druginduced hepatotoxicity, especially inclusive of acetylaor phenotype polymorphism, have been increasingly unravelled. Other principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
159
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 66 publications
3
159
2
9
Order By: Relevance
“…In this study the incidence of DIH was similar to the rates reported in previous studies (5,6,20,21). Several risk factors for anti-TB DIH, such as old age, female gender, malnutrition, alcoholism, underlying liver disease, extensive pulmonary parenchymal disease, and HIV infection, have been reported in previous studies (5,6,22,23). The findings obtained in this study were inconsistent with these known risk factors.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In this study the incidence of DIH was similar to the rates reported in previous studies (5,6,20,21). Several risk factors for anti-TB DIH, such as old age, female gender, malnutrition, alcoholism, underlying liver disease, extensive pulmonary parenchymal disease, and HIV infection, have been reported in previous studies (5,6,22,23). The findings obtained in this study were inconsistent with these known risk factors.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the N-acetylator level could be determined indirectly through the metabolite level, which was also analyzed by TDM in the present study. Lastly, dose-related toxicity is not the only possible cause of DIH; idiosyncratic reactions, oxidative stress, or hypersensitivity to anti-TB drugs may also lead to DIH in some cases (22,23). More research using TDM is needed to evaluate the TB drug plasma concentration and hepatotoxicity response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…INH and its metabolites have been implicated in hepatotoxicity in humans (Huang et al, 2003), and in an in vitro model of human hepatocellular carcinoma cell line (HepG2 cells) (Wu and Cederbaum, 1996). RIF, which is usually co-administered with INH, synergises the hepatotoxicity of INH, possibly due to its potent induction of CYP 450 enzymes thereby increasing the production of toxic metabolite hydrazine (HYD) (Yew, 2002;Yew and Leung, 2006). Several studies have also implicated the role of PYZ in the development of ATTinduced drug hepatotoxicity (Yee et al, 2003;Schaberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of hepatic excretion of bilirubin, associated with lipid accumulation, has been observed in rats but not in humans (Adachi et al 1985;Piriou et al 1987). Although rifampicin is a potential inducer of hepatic CYP 450s (Yew and Leung 2006;De Rosa et al 2007), it is not clear that such CYP 450s are involved in rifampicin toxicity, but CYP 3A was suggested (Rana et al 2006). Different from the evident hepatotoxicity of rifampicin in vivo, a lack of toxicity was demonstrated in rifampicin-treated hepatocytes in vitro.…”
mentioning
confidence: 89%
“…It appears that gel-entrapped rat hepatocytes reflected significant hepatotoxicity of rifampicin in vivo, and this toxicity was most possibly associated with oxidative stress and lipid accumulation. Rifampicin, an antitubercular drug, is largely considered to enhance toxicity of other antitubercular drugs (such as isoniazid and pyrazinamide) due to its potent induction on cytochrome P (CYP) 450 (Yew and Leung 2006). Meanwhile, it is well known that the use of rifampicin alone causes liver damage in humans (Yew and Leung 2006), rats (Adachi et al 1985;Sodhi et al 1997;Rana et al 2006), mice (Upadhyay et al 2007), and rabbits (Karthikeyan 2005;Kalra et al 2007).…”
mentioning
confidence: 95%